Formal and Informal Language Use among University Students: A Sociolinguistic Analysis (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article explores the distinctions between formal and informal language, focusing on their unique features, intended purposes, and appropriate usage contexts. Informal language tends to be more relaxed, spontaneous, and commonly used in casual conversations. In contrast, formal language is structured, respectful, and predominantly employed in academic, professional, and official environments. The study emphasizes how choosing the right language style impacts communication by affecting clarity, tone, and overall effectiveness. The differences between vocabulary choices, grammatical structures, and communicative intentions are examined to show how language style influences interaction. Understanding when to use formal or informal language enables speakers and writers to adapt more easily to various social situations. This adaptability not only improves communication but also helps in fostering better understanding across different contexts, ensuring that the message is received in the intended manner. By mastering the appropriate use of both language styles, individuals can enhance their communication skills and navigate diverse social settings more effectively.